ANALISIS PROFITABILITAS KERIPIK PISANG PADA INDUSTRI â€œCAHAYA INDIâ€ DI DESA TANAMEA KECAMATAN BANAWA SELATAN KABUPATEN DONGGALA - Fitrianingsih, Eka (AGROTEKBIS, 2019)
This research aimed to find out the total cost, acceptance, revenue and profits of Banana Chips at Cahaya Indi Industry. The research was carried out in Banawa village, South Tanamea sub-district, Donggala district of Central Sulawesi province from June-August 2016. One leader and two employees of the industry were interviewed. The industry profitability was analyzed using Gross Profit Margin (GPM), Net Profit Margin (NPM), and Return on Equity (ROE). The results showed that during 2015-2016, the GPM, NPM, and ROE values were 43.42%, 42.93%,and 20.81%, respectively.